2009
DOI: 10.1055/s-0029-1237732
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Thyroid Hormones; Insulin-like Growth Factor-1 (IGF-1), IGF Binding Proteins, and Nutritional Anthropometric Parameters in School Children with Goiter Detected by Palpation

Abstract: In endemic areas, children with palpable goiter were shorter and thinner than the healthy peers. Thyroid hormones were between the reference ranges. In children with palpable goiter, IGF-1 levels were lower and IGFBP-3 and IGFBP-1 levels were not different from the healthy control group. However, at the presence of goiter IGF-1 levels decrease. This decrease can be the result of insufficient nutrition and result in short stature and weakness than their healthy peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A study on children with simple goiter showed that serum IGF-1 levels in children with goiter were lower than those children without goiter, reflecting that low-levels of IGF-1 in serum may be associated with thyroid enlargement [18]. The Völzke et al’s study [19] disclosed that the occurrence of thyroid nodules was associated with the high level of IGF-1 in serum, however, that was only observed in male patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study on children with simple goiter showed that serum IGF-1 levels in children with goiter were lower than those children without goiter, reflecting that low-levels of IGF-1 in serum may be associated with thyroid enlargement [18]. The Völzke et al’s study [19] disclosed that the occurrence of thyroid nodules was associated with the high level of IGF-1 in serum, however, that was only observed in male patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the study by Du et al concluded in controversial results demonstrating a negative correlation between IGF1 expression and thyroid nodular disease; however, due to the fact that the nature of the nodules (benign or malignant) was not known this posed a limitation in the study (9). Nevertheless, in line with Du et al, Ersoy et al showed lower IGF1 serum levels in children with goiter compared to children without goiter (57).…”
Section: Discussionmentioning
confidence: 92%